Distinct modes of manipulation of rice auxin response factor OsARF17 by different plant RNA viruses for infection - Zhang, Hehong; Li, Lulu; He, Yuqing; Qin, Qingqing; Chen, Changhai; Wei, Zhongyan; Tan, Xiaoxiang; Xie, Kaili; Zhang, Ruifang; Hong, Gaojie; Li, Jing; Li, Junmin; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Plant auxin response factor (ARF) transcription factors are an important class of key transcriptional modulators in auxin signaling. Despite the well-studied roles of ARF transcription factors in plant growth and development, it is largely unknown whether, and how, ARF transcription factors may be involved in plant resistance to pathogens. We show here that two fijiviruses (doublestranded RNA viruses) utilize their proteins to disturb the dimerization of OsARF17 and repress its transcriptional activation ability, while a tenuivirus (negative-sense single-stranded RNA virus) directly interferes with the DNA binding activity of OsARF17. These interactions impair OsARF17-mediated antiviral defense. OsARF17 also confers resistance to a cytorhabdovirus and was directly targeted by one of the viral proteins. Thus, OsARF17 is the common target of several very different viruses. This suggests that OsARF17 plays a crucial role in plant defense against different types of plant viruses, and that these viruses use independently evolved viral proteins to target this key component of auxin signaling and facilitate infection.